Enzyme-mediated hydrolytic activation of prodrugs - Yan-hui Yang; Herve Aloysius; Daigo Inoyama; Yu Chen; Long-qin Hu (Elsevier, 2011)
Prodrug design is an important part of drug discovery. Prodrugs can offer many advantages over parent drugs such as increased solubility, enhanced stability, improved bioavailability, reduced side effects, and better selectivity. Many prodrugs have been used successfully in the clinic; examples include oseltamivir in anti-influenza therapy, enalapril in anti-hypertension therapy, capecitabine in cancer therapy, and omeprazole in the treatment of peptic ulcer. A key step in prodrug design is the incorporation of an activation mechanism that can convert the prodrug into the active species in an efficient and/or controlled manner to meet the needs of a given medical application. Prodrug activation can be achieved through enzyme-mediated hydrolytic or oxidoreductive processes while activation of some prodrugs may proceed through pure chemical nonenzymatic processes. This review focuses on the hydrolytic enzymes that have been used in prodrug activation, including transferases, hydrolases, and lyases.